POSTEMBRYONIC DEVELOPMENT AND VARIOUS GROWTH INDICES OF WHITE GRUB BEETLE, HOLOTRICHIA CONSANGUINEA BLANCH ON KHEJRI, BER AND NEEM - SINGHKUNTAL, JAGBIR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The postembryonic stages including incubation period, grub and pupal duration and adult longevity are shorten and various growth indices were found best on Khejri host plant (most preferred) as compared to Ber and Neem.